On the optimal design of consumption taxes - Michael Barczay (Swiss National Bank, Study Center Gerzensee, 2025)
This paper studies the optimal design of differentiated consumption taxes in the presence of progressive labor income taxes and capital income taxation. A quantitative heterogeneousagent model with non-homothetic preferences and uninsurable idiosyncratic risk is estimated using US consumption and price data to match expenditure patterns across the income distribution. Solving the Ramsey problem in which the government jointly chooses labor income and commodity taxes, the optimal policy prescribes a subsidy on necessities of -52% and a positive tax of 7% on luxuries, accompanied by a reduction in labor tax progressivity. Three mechanisms account for these results: subsidized necessities provide consumption insurance, taxation of luxuries acts as an implicit tax on existing wealth, and differentiated rates strengthen labor supply incentives among highly productive households.
Keywords: E21; E62; H21; H23; H31; 330; Heterogeneous Agents; Fiscal Policy; Optimal Taxation; Redistribution